Pemberdayaan Masyarakat Melalui Perkawinan Adat Jawa (Studi Kasus Masyarakat Suku Jawa di Kota Duri Kabupaten Bengkalis RIAU) - rudi haryanto (STAI Hubbulwathan Duri, 2018)
The Javanese tribe Duri community still carries out the Javanese traditional wedding ceremony. Although there were some people who did not carry out the Javanese traditional wedding ceremony. However, it often feels incomplete if the traditional Javanese wedding party without a ceremonial ceremony even though most of the Javanese Duri people do not know the meaning contained in the Javanese traditional wedding rituals, which is clear if the bride and groom carry out Javanese traditional wedding ceremonies certainly have played a role in preserving customs Javanese culture. Javanese traditional wedding ceremony is preceded by mayang twins, balangan, wiji dadi, sungkeman, sindur binayang, tanem, dahar kembul, pull-tug roast chicken and fresh flour.